The effects of female labor force participation on obesity - Pedro Gomis-Porqueras; Oscar A. Mitnik; Adrian Peralta-Alva; Maximilian D. Schmeiser (Institute for the Study of Labor (IZA), 2011)
This paper assesses whether a causal relationship exists between recent increases in female labor force participation and the increased prevalence of obesity amongst women. The expansions of the Earned Income Tax Credit (EITC) in the 1980s and 1990s have been established by prior literature as having generated variation in female labor supply, particularly amongst single mothers. Here, we use this plausibly exogenous variation in female labor supply to identify the effect of labor force participation on obesity status. We use data from the National Health Interview Survey (NHIS) and replicate labor supply effects of the EITC expansions found in previous literature. This validates employing a difference-in-differences estimation strategy in the NHIS data, as has been done in several other data sets. Depending on the specification, we find that increased labor force participation can account for at most 19% of the observed change in obesity prevalence over our sample period. Our preferred specification, however, suggests that there is no causal link between increased female labor force participation and increased obesity.
urn:nbn:de:101:1-201111083046
Keywords: H31; I12; J22; 330; female labor force participation; obesity; earned income tax credit; Weibliche Arbeitskräfte; Erwerbstätigkeit; Körpergewicht; Arbeitsangebot; Steuerbegünstigung; Schätzung; USA